2021
DOI: 10.17816/vto65076
|View full text |Cite
|
Sign up to set email alerts
|

Surgical rehabilitation of patients with the consequences of pilon fractures

Abstract: BACKGROUND: Pilon fracture is an intra-articular injury of tibia distal metaepiphysis; its often comminuted. Comprehensive reconstruction of the tibia articular surface and recovery of the axil in the affected extremity is of prime importance for the rehabilitation of patients with such pathology, so priority is given to reconstructive surgical techniques. Pilon injury often causes deforming arthrosis of the ankle joint that reduces its functions. It is ankle arthrodesis that is considered to be the preferred … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 6 publications
0
1
0
Order By: Relevance
“…In addition, a significant therapeutic challenge is the effective management of complications following intra-articular fractures of the distal tibia. The researchers Grazhdanov et al [11] found that there must be a consistent treatment protocol that takes into account the many surgical options (such as ORIF), and their indications and contraindications. Finally, it is important to be cautious when using ORIF, and take into account patient characteristics and potential repercussions, even though it remains a basic strategy for treating displaced intra-articular fractures.…”
Section: Figurementioning
confidence: 99%
“…In addition, a significant therapeutic challenge is the effective management of complications following intra-articular fractures of the distal tibia. The researchers Grazhdanov et al [11] found that there must be a consistent treatment protocol that takes into account the many surgical options (such as ORIF), and their indications and contraindications. Finally, it is important to be cautious when using ORIF, and take into account patient characteristics and potential repercussions, even though it remains a basic strategy for treating displaced intra-articular fractures.…”
Section: Figurementioning
confidence: 99%